A New Methodology to Analyze Instabilities in SEM Imaging. (20th October 2014) - Mansilla, Catalina; Ocelík, Václav; De Hosson, Jeff T. M.
Abstract This paper presents a statistical method to analyze instabilities that can be introduced during imaging in scanning electron microscopy (SEM). The method is based on the correlation of digital images and it can be used at different length scales. It consists of the evaluation of three different approaches with four parameters in total. The methodology is exemplified with a specific case of internal stress measurements where ion milling and SEM imaging are combined with digital image correlation. It is concluded that before these measurements it is important to test the SEM column to ensure the minimization and randomization of the imaging instabilities. The method has been applied onto three different field emission gun SEMs (Philips XL30, Tescan Lyra, FEI Helios 650) that represent three successive generations of SEMs. Important to note that the imaging instability can be quantified and its source can be identified.